Respiratory effort perception at rest and during carbon dioxide rebreathing in patients with dystrophia myotonica. Issue 3 (March 1994) - Clague, J E; Carter, J; Coakley, J; Edwards, R H; Calverley, P M
Abstract : BACKGROUND--Breathlessness appears to be closely related to the perception of the outgoing motor command to breathe and should be increased in the presence of muscle weakness. However, breathlessness is not a common symptom in patients with chronic muscle disease who have weak respiratory muscles. The factors that determine the perception of respiratory effort in such patients have not been examined. METHODS--The inspiratory effort sensation during resting breathing and progressive hypercapnia was investigated in 12 patients with dystrophia myotonica with weak respiratory muscles (nine men and three women of mean (SD) age 41.1 (10.5) years; maximum inspiratory pressure 43.1 (17.2) cm H2O) and an age and sex matched control group of normal subjects of mean age 39.6 (10.6) years and a maximum inspiratory pressure of 123 (15.2) cm H2O. RESULTS--During resting breathing with a mouthpiece no differences were seen in inspiratory effort sensation, mouth occlusion pressure, or tidal volume, but inspiratory time and cycle duration were significantly shorter in the patients with dystrophia. Minute ventilation (VE) was significantly higher in the patients (15.8 (4.0) l/min v 12.5 (2.6) l/min), while resting breathing was no more variable in the patients than in controls. The ventilatory response to carbon dioxide (VE/PCO2) was not significantly lower in the patients (14.9 (6.9) l/min/kPa) than in the controls (17.4 (4.3) l/min/kPa). Effort sensation responses to carbon dioxide driven breathing were similar in the control subjects and the patients. With regression analysis of pooled data neither maximum inspiratory pressure nor disease state contributed to perceived inspiratory effort during hypercapnia. CONCLUSIONS--Moderately severe global respiratory muscle weakness does not appear to influence the ventilatory response to rising carbon dioxide tension or the perception of inspiratory effort in patients with dystrophia myotonica.